IgG4-Related Disease: The Importance of Early Diagnosis in Clinical Practice - Zawadzka, Magdalena; Gwóźdź, Karolina; Drozdowska, Marta; Bystros, Aleksandra Natalia; Borychowska, Emilia; Czudowska, Michalina; Mierzejewska, Zofia Aneta; Ocimek, Aleksandra; Kurzątkowska, Klaudia; Marszałek, Dominika (Journal of Education, Health and Sport, 2025)
Background: IgG4-related disease (IgG4-RD) is a chronic immune-related fibroinflammatory disease characterized by multiorgan involvement and a highly heterogeneous clinical presentation, often mimicking malignant, infectious, or autoimmune conditions. These features contribute to frequent diagnostic delays and can lead to irreversible organ damage. Aim: To summarize the current evidence on the pathogenesis, clinical manifestations, diagnostic approach, and treatment of IgG4-RD, with particular emphasis on the importance of early diagnosis in clinical practice. Material and Methods: A review of medical literature published between 2015 and 2025 was conducted using major bibliographic databases, including PubMed. The search covered articles released within this period and employed the following keywords and their combinations: “IgG4-related disease”, “IgG4-RD”, “autoimmune pancreatitis”, “retroperitoneal fibrosis”, “IgG4-related kidney disease”. Results: IgG4-RD most commonly affects the salivary and lacrimal glands, pancreas, bile ducts, kidneys, and retroperitoneal space. Delayed diagnosis of the disease is associated with progression of fibroinflammatory changes and permanent organ dysfunction. Glucocorticoids remain first-line therapy, while immunosuppressive drugs and rituximab are effective options in case of recurrence or resistance to treatment. Data from clinical cohorts indicate that the lack of early immunosuppression significantly increases the risk of organ failure. Conclusions: IgG4-RD should be routinely considered in the differential diagnosis of unexplained mass lesions or chronic inflammatory and fibrotic disorders. Early diagnosis and prompt initiation of immunosuppressive therapy are crucial for preventing irreversible organ damage and improving patient outcomes.